Motion paths finding for multi-degree-of-freedom mechanisms - Li, Yang (International journal of mechanical sciences, 2020)
•This paper (together with submitted codes) provides a comprehensive numerical toolbox for generating different motion paths of multi-degree-of-freedom (multi-DOF) mechanisms.•Path-finding analysis is conducted, which can find paths that connect the current configuration with the target configuration for multi-DOF mechanisms with (almost) arbitrary complexity.•The analysis is able to find multiple kinematic paths with different features based on user’s preferences. [Display omitted] Multiple degree-of-freedom (DOF) mechanisms can provide more flexible reconfigurations than 1 DOF ones but are more complex to analyze. One difficulty is the existence of an unlimited number of valid motion directions at each configuration point. In this paper, a shooting method that is defined by customized target functions is introduced to help determine a specific motion direction at each configuration point. As a result, an incremental path-finding simulation can be carried out by following a unique motion direction at each step. The ability to arbitrarily define the target function allows a flexible and desirable exploration of the motion space, and it can find different motion paths that lead to the target state. Two examples are provided, in which different motion paths for deploying a 5-bar linkage and folding a Resch origami pattern are generated.